COVID‐19 Interconnectedness: Health Inequity, the Climate Crisis, and Collective Trauma. Issue 3 (3rd August 2020) - Watson, Marlene F.; Bacigalupe, Gonzalo; Daneshpour, Manijeh; Han, Wen‐Jui; Parra‐Cardona, Rubén
Abstract : The COVID‐19 pandemic brings to the forefront the complex interconnected dilemmas of globalization, health equity, economic security, environmental justice, and collective trauma, severely impacting the marginalized and people of color in the United States. This lack of access to and the quality of healthcare, affordable housing, and lack of financial resources also continue to have a more significant impact on documented and undocumented immigrants. This paper aims at examining these critical issues and developing a framework for family therapists to address these challenges by focusing on four interrelated dimensions: cultural values, social determinants of health, collective trauma, and the ethical and moral responsibility of family therapists. Given the fact that family therapists may unwittingly function as the best ally of an economic and political system that perpetuates institutionalized racism and class discrimination, we need to utilize a set of principles, values, and practices that are not just palliative or after the fact but bring forth into the psychotherapeutic and policy work a politics of care. Therefore, a strong call to promote and advocate for the broader continuum of health and critical thinking preparing professionals to meet the challenges of health equity, as well as economic and environmental justice, is needed. The issues discussed in this paper are specific to the United States despite their relevance to family therapy as a field. We are mindful not to generalize the United States' reality to the rest of the world, recognizing that issues discussed in this paper could potentially contribute to international discourse. Resumen: La pandemia de la COVID‐19 ha puesto en primer plano los dilemas complejos e interconectados de la globalización, la equidad sanitaria, la seguridad económica, la justicia ambiental y el trauma colectivo, afectando gravemente a las personas marginadas y de color de los Estados Unidos. Esta falta de acceso a asistencia sanitaria de calidad, a viviendas asequibles, y la falta de recursos económicos también continúan teniendo un efecto más significativo en los inmigrantes documentados e indocumentados. Este artículo tiene como finalidad analizar estas cuestiones críticas y desarrollar un marco para que los terapeutas familiares aborden estas dificultades centrándose en cuatro dimensiones interrelacionadas: valores culturales, determinantes sociales de salud, trauma colectivo, y responsabilidad ética y moral de los terapeutas familiares. Teniendo en cuenta el hecho de que los terapeutas familiares pueden funcionar inconscientemente como los mejores aliados de un sistema económico y político que perpetúa el racismo institucionalizado y el clasismo, necesitamos utilizar un conjunto de principios, valores y prácticas que no sea solo paliativo o a posteriori, sino que genere en el trabajo político y psicoterapéutico una política de asistencia. Por lo tanto, es necesario un reclamo firme de promover y abogar por un continuo más amplio de la salud y un pensamiento crítico que prepare a los profesionales para responder a las dificultades de la equidad sanitaria, así como de la justicia económica y ambiental, si fuera necesario. Las cuestiones tratadas en este artículo son específicas de los Estados Unidos a pesar de su relevancia para la terapia familiar como área. Somos conscientes de no generalizar la realidad de los Estados Unidos para el resto del mundo, y reconocemos que las cuestiones tratadas en este artículo podrían contribuir al discurso internacional. 摘要: 新冠肺炎疫情让全球化、健康公平、经济安全、环境正义和集体创伤等相互关联的复杂困境变得愈发显著，严重影响着美国的边缘化人群和有色人种人群。对有正规记录的移民和无记载的移民们来说，很少有机会得到医疗保健且缺乏有质量的医保、买不起住房加上资金财力匮乏等等诸多因素都在持续对他们产生更严重的影响。本文旨在探讨这些关键问题，并通过关注四个相互关联的维度来为家庭治疗师建立一个框架以应对这些挑战。该四个维度指 文化价值观、健康的社会决定因素、集体创伤以及家庭治疗师的伦理和道德责任。鉴于家庭治疗师可能在不知不觉中成为经济和政治制度的最佳盟友，这种体制里有制度化的种族主义和阶级歧视。我们需要利用一套原则、价值观和做法，它们不仅仅是缓和性的或事后的，而是将关怀政治带入心理治疗和政策工作中的。因此，需要强烈呼吁促进和倡导更广泛的连续统一的健康和批判性思维，使专业人员做好准备，迎接健康公平以及经济和环境正义的挑战。我们很清楚不必要将美国的现实推广到世界其他国家，也认识到本文中讨论的问题可能有助于国际范围内的讨论。